High performance computing for big data methodologies and applications - Wang, Chao (Chapman & Hall/CRC big data series, 2018)
High-Performance Computing for Big Data: Methodologies and Applications explores emerging high-performance architectures for data-intensive applications, novel efficient analytical strategies to boost data processing, and cutting-edge applications in diverse fields, such as machine learning, life science, neural networks, and neuromorphic engineering.